Closed venereology wards in postwar Hamburg. (23rd February 2020) - Schochow, M.; Bjoernsgard, K.; Orzechowski, M.; Steger, F.
Abstract: Background: A number of research results on closed venereology facilities in the Soviet Occupation Zone (SOZ) and the German Democratic Republic (GDR) have been presented in recent years. However, little is known about similar facilities in the Western Occupation Zones (WOZ) and in the early Federal Republic of Germany (FRG). Method: We have researched the records of the State Archive in Hamburg. Subsequently, the analysed sources were evaluated using the historically critical method. Results: Three closed venereology wards existed in Hamburg. Compulsory commitments were conducted according to a three‐stage procedure. In the immediate postwar period, the wards had barred windows and the doors were locked. Everyday life in the wards was initially determined by the postwar situation – poor facilities, poor hygiene, overcrowding. In the early 1950s, the number of beds was drastically reduced. The function of the wards consisted of isolation and medical care for the compulsorily committed persons. Medical care was in accordance with professional medical standards. Discussion: Closed venereology wards in Hamburg followed the tradition established during the period of the Weimar Republic. This becomes apparent both in terms of the legal framework and in terms of the structure and functions of the wards. Thus, they clearly differ from the closed venereology facilities in the SOZ and in the GDR. These facilities were established in the tradition of Soviet prophylactics institutions. The wards in Hamburg served as isolation and treatment centres, the facilities in the SOZ and in the GDR also had a disciplinary function.